Bills of Quantities (BQ) decrypted: uncovering research findings on BQ information requirements and the way forward - Bandi, Shamsul Hadi (2015)
There have been concerns identified on the inadequacy of the BQ for utilisation by the contractors. These as contractors are constantly baffling to relate the BQ to the project development process thus resulting to the great loss of its utility during the construction process. In the midst of these concerns, information has been perceived to characterise issues concerning its use to the contracting organisations. This prompted a research to be conducted with the ultimate aim to develop a conceptual framework that indicates the important BQ information requirements and significant issues to be considered as the basis to improve the uses of the BQ. In relation to the research that has been carried out, this paper reports an excerpt from the research and is focused to highlight findings on determining the BQ information requirements to the identified usage of the BQ. Accordingly, nine information has been considered important to the uses of BQ. These are ranked as: (1) Quantities; (2) Time/duration; (3) Work descriptions; (4) Quantity units; (5) Unit rates; (6) Material specifications; (7) Working methods; (8) Preliminaries and (9) Provisional sums. The results suggest that ‘quantities’ has an important position to the overall uses of the BQ. This implies that more effort should be expanded to study about ‘quantities’ given its substantial contribution to the management of construction works.